Geography Textbooks in the Opinion of Secondary School Students–A Polish Case Study - Tracz, Mariola (Journal of Geography Education, 2016)
Geography textbooks experience an ongoing change of their content and layout. Structure, content, and layout carry a specific educational concept and become the source of information available to students. This paper aims at mapping student opinion on geography textbooks currently used in Polish lower and upper secondary education. A total of twelve randomly selected lower secondary and fourteen upper secondary schools facilitated the questionnaire-based data collection. The sample consisted of 2,681 student responses. Data collection focused, among others, on student opinion on geography textbooks selected by their teachers, their usage during the process of teaching and learning, as well as their role in motivating students to develop an interest in geography. The results show an overall positive evaluation regarding textbook layout. In contrast, most students criticized content, tasks, and language.